PERSONALITY TYPES AND DEPRESSION AMONG MEDICAL STUDENTS IN UniKL RCMP - Hussain R.A. Saadi; Raja Anis Syafiqah bt Raja Abdul Rahman; Ami Farah Bt Amir Abdul Nasir; Nilam Maisarah binti Kassim (Asian Journal of Medicine & Health Sciences, 2020)
Background: The prevalence of depression among medical students is not uncommon. It usually happens because of the transition from a normal school environment to the medical college environment, where, the students need to be independent in taking care of themselves in terms of daily living and their studies. The aim of the study was to find out the association between the personality type and depression among medical students. Methodology: The study was a cross-sectional study among 186 respondents, chosen based on convenience. A set of questionnaires consisting of three parts to assess their sociodemographic input, degree of depression and types of personality were prepared and distributed in the campus among the clinical year medical students only (Year 3, 4 and 5). The study was conducted over a period of 1 week in March 2017 in RCMP in Ipoh. Results: Most of the students were found to be having the personality of openness to experience with the mean score of 32.98 and have normal degree of depression with the percentage of 73.7%. Female students were relatively more depressed than males. More students in Year 3 were depressed compared to the Year 4 and Year 5 and more Malay respondents were positive for depression compared to the other races. Overall, there was no significant association between these sociodemographic factors and the degree of depression and also between the gender and type of personality. Finally, it was found that the association between the types of personality and the degree of depression was statistically significant. Conclusion: This study found that the type of personality of an individual would influence the degree of depression. However, more such studies should be conducted to explore more about the types of personality, the reaction towards stressor and development of depression as the type of personality is an important aspect in determining how they adapt to the stress, which, if they fail to handle, they may develop the symptoms of depression.